2015
DOI: 10.1109/tgrs.2015.2420996
|View full text |Cite
|
Sign up to set email alerts
|

Forest Height Estimation by Means of Pol-InSAR Data Inversion: The Role of the Vertical Wavenumber

Abstract: This paper examines the multifaceted effect of the effective spatial baseline, as expressed through the vertical (interferometric) wavenumber, on the inversion of forest height from polarimetric interferometric synthetic aperture radar (Pol-InSAR) data. First, the role of the vertical wavenumber in relating forest height to the interferometric (volume) coherence is introduced. Through the review of the forest height inversion from Pol-In-SAR data, the effect of the vertical wavenumber on the inversion performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 71 publications
3
159
0
Order By: Relevance
“…which provides the equation as a product of the imaginary and real functions [45]. As can be noted from (7) and (8), a convenient argument for this problem is not h, but hκ z .…”
Section: Rvog Model Simplificationsmentioning
confidence: 99%
“…which provides the equation as a product of the imaginary and real functions [45]. As can be noted from (7) and (8), a convenient argument for this problem is not h, but hκ z .…”
Section: Rvog Model Simplificationsmentioning
confidence: 99%
“…Kugler et al evaluated the multifaceted effect of the effective spatial baseline by analyzing the vertical wavenumber (Kz). He concluded that a good choice to get reliable forest height estimates with sufficient accuracy for single baseline acquisitions is to select Kz ranging from 0.05 to 0.15 rad/m [60]. According to our statistics of five pairs of PolInSAR datasets in the two flight directions, we found that the baselines of 32 m in both two flight directions can better fulfill the above condition of Kz.…”
Section: Polarimetric Sar Datamentioning
confidence: 76%
“…If the angle of the range-facing terrain slope is denoted as τ c , we can attempt to partially correct for the effects of the range slope by calculating k z as follows, in the monostatic (repeat-pass) case [7,8]:…”
Section: Methodsmentioning
confidence: 99%